Elements of Pure Accounting Theory. - Sterling, Robert R. (The Accounting Review, 1967)
The article analyzes the present accounting theory. The concept of service-potentialities is well established in accounting. They are thought to be the homogeneous substance and the significant elements of assets. Thus, assets may be thought of as a set, the elements of which are service-potentialities. The concept of capacity, although only relatively recently named, has been used in accounting since, at least, the advent of depreciation. Assets are thought of as bundles of services and the number of services in most assets declines over time or use. Cap is the generic term for all the various units of measure that are used in accounting. The concept of account is best described as a homogeneous collection of caps. Different accounts will contain different kinds of caps and the accounts may contain different physical representations of the caps, but each account will contain only one kind of cap. The functional relationship between the quantities of caps in an exchange may be determined by a measurement operation or by a similarity transformation.